Diagnostic accuracy of haemoglobin colour strip (HCS-HLL), a digital haemoglobinometer (TrueHb) and a non-invasive device (TouchHb) for screening patients with anaemia. Issue 2 (14th August 2015) - Neogi, Sutapa Bandyopadhyay; Negandhi, Himanshu; Kar, Rakhee; Bhattacharya, Maitrayee; Sen, Rajeev; Varma, Neelam; Bharti, Priyanka; Sharma, Jyoti; Bhushan, Himanshu; Zodpey, Sanjay; Saxena, Renu
Abstract : Aim: Estimation of haemoglobin (Hb) remains a challenge, particularly in outreach settings. There is a need to have a simple and cost-effective device to detect anaemia. Three devices (haemoglobin colour scale (HCS)-HLL (Hindustan Lifecare Limited), TrueHb V.1.1, TouchHb Alpha 1.1- non-invasive) have been developed in India recently. This study aimed to determine the diagnostic accuracy of these tests (index) for the screening of anaemia against haematological autoanalyzer (reference). Methods: The study was conducted in four medical colleges of India. All consenting adult patients (>18 years of age) undergoing routine investigations were included. Each patient underwent the reference test and at least one index test. Outcome assessors for the index tests were blinded to the results of the reference test. Diagnostic accuracy was calculated using cut-offs proposed by WHO. Results: A total of 5244 patients underwent the reference test while HCS-HLL, TrueHb and TouchHb tests were conducted on 2745, 2331 and 2874 patients respectively. The positive likelihood ratio of HCS-HLL using capillary blood (1.2), venous blood (1.7) and TouchHb (1.5) was lower than TrueHb capillary (3.7; 95% CI 3.3 to 4.2) and venous blood (5.7; 95% CI 4.9 to 6.6). TrueHb had a sensitivity of 74.4% (95% CI 71.9% to 76.8%) for venous and 82.0% (95% CI 79.8% to 89.2%) for capillary samples. The specificity was high (>75.0%). The area under receiver operating characteristic was close to 80.0%. Consistent results were seen for detection of severe anaemia. Conclusions: The digital method (TrueHb) emerged as a better diagnostic method for screening anaemia. Its effectiveness should be established in outreach settings before further recommendation.